A New Repair Technique in Pronator Quadratus in Management of Distal Radius Fracture: Comparison with Primary Repair and Unrepaired Techniques - Ayik, Ömer; Bayram, Serkan; Altan, Murat; Engin, Muhammed Çağatay (Journal of Wrist Surgery, 2023)
Objective We aimed to compare the functional and clinical results between our new repair technique in the groups with and without pronator quadratus (PQ) repair in distal radius fractures treated with plate fixation using the volar approach.Methods The medical records of patients who underwent open reduction and volar plate fixation due to distal radius fracture between 2018 and 2020 were studied. In group A, PQ cannot be sutured or tension may occur, the intact radial fascia of the deep anterior fascia (DAF) was placed under the flexors toward the PQ and it was sutured with a 3-0 slow-absorbable monofilament suture to DAF. In group B, no repair was performed. In group C, PQ was sutured with traditional method. Range of motion (ROM) of wrist and handgrip strengths were measured at final examination. Pain was assessed with Visual Analogue Score (VAS), and functional status was evaluated with Quick - Disabilities of the Arm, Shoulder, and Hand (DASH). Complications which included tendinopathy, neuritis, tendon rupture due to plate irritation, implant failure, and malunion were also compared.Results Seventy-seven patients (group A, 21, group B, 24, group C, 32 patients) were included in the final follow-up examination who met our inclusion criteria. Among the clinical, functional, and radiological results such as ROM, VAS, DASH, grip strength, and complications in the all group at a mean postoperative of 16.6 months no significant difference was observed.Conclusion Although there was no significant difference between the groups in this study, we think that covering the plate may prevent long-term complications.
Keywords: pronator quadratus; fascia; distal radius fracture; complications